STRATEGI PEMASARAN PRODUK TEH CASCARA DI PT AGRITAMA SINERGI INOVASI KOTA BANDUNG - Muhammad Ardian; Kuswarini Kusno (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
PT Agritama Sinergi Inovasi is a company that produces tea from coffe husk which is commonly called cascara. Cascara product sales are unstable and tend to stagnate during 2020–2021. Thus, it is necessary to identify the causes of the low sales of cascara tea in order to formulate the marketing strategy of the cascara tea in PT Agritama Sinergi Inovasi. This study uses case study techniwues. Primary and secondary data are collected through observation, interviews and literature studies. Data on srengths, weaknesses, opportunities and threats encountered by PT Agritama Sinergi Inovasi were analyzed using SWOT Analysis and Quantitative Strategic Planning (QSP) Matrix. As a result, there were seven strategies: 1) ofline marketing to reach the target market, 2) Actively conducting education in the upstream and downstream sectors, 3) Using KPI and implementing punishment and reward, 4) recruiting employees to focus on b to b, 5) conduct a comprehensive record of income and epenses as evaluation material, 6) make agreements with suppliers and offer supply of cascara, and 7) conduct research and recommendations on resellers related to product for online sales. The best strategy recommendations is strategy number 2) mentioned above.